Relationship between Mycoplasma mycoides subsp. mycoides ('Large-colony' Strains) and M. mycoides subsp. capri, as Indicated by Numerical Analysis of One-dimensional SDS-PAGE Protein Patterns - Leach, R. H; Costas, M; Mitchelmore, Deborah L (Journal of general microbiology, 1989)
National Collection of Type Cultures, Central Public Health Laboratory, Colindale Avenue, London NW9 5HT, UK PHLS Mycoplasma Reference Facility (NCTC), Central Public Health Laboratory, Colindale Avenue, London NW9 5HT, UK ABSTRACT Summary: Twenty-five strains classified as Mycoplasma mycoides subsp. mycoides LC or subsp. capri have been compared by one-dimensional SDS-PAGE of their cellular proteins. A computerized numerical analysis revealed that the protein patterns of all but two aberrant strains formed one large phenon that separated clearly from representatives of the four other members of the M. mycoides cluster at a similarity level ( S ) of 66% and which remained undivided at up to 78% S . At higher similarity levels, these strains fell heterogeneously into mixed sub-phenons containing strains of both subspecies. Serological comparisons by immunofluorescence largely confirmed the subspecies designations of the test strains, but also showed that some were serologically intermediate between subsp. mycoides and subsp. capri , being cross-reactive with both. These results confirm and enlarge upon those of our earlier studies indicating the protein-pattern inseparability of subsp. capri and subsp. mycoides LC strains and their distinctiveness from the classical M. mycoides subsp. mycoides SC strains and other members of the M. mycoides cluster. As also recognized by other workers, subsp. mycoides LC and subsp. capri strains appear to comprise one large group, wherein those most readily identifiable as either type lie at either end of a serological spectrum that also contains serologically cross-reactive strains. Our observations therefore suggest the lines along which the three groups classified at present within the species M. mycoides (SC and LC strains of subsp. mycoides; subsp. capri ) might eventually be reclassified, subject to direct genomic comparisons.